Hubungan Pola Asuh Orang Tua Dengan Status Gizi Pada Balita Usia 1 - 5 Tahun di Desa Selokgondang Kecamatan Sukodono Kabupaten Lumajang - Hidayathillah, Ariska Putri; Mulyana, Eni (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2018)
The ages of 1-5 years (toddlers) is the period in which the child is in need of food and nutrition in sufficient amount and adequate. Nutritional deficiencies during this time can cause interference to grow flowers. At this time also, the child is still totally dependent on the care and upbringing by his mother. Research objectives: knowing parents parenting relationship with nutritional status on toddlers in the village of Selokgondang Sub Lumajang Sukodono in 2017. The type of research that is used is a type of analytic survey research (kolerasi) by using the Cross-Sectional design. The sample in this research are all parents and toddlers in the village of Selokgodang Sub Lumajang Sukodono as much as 62 respondents. Most toddlers have a good nutritional status IE as much as 69.4%, parenting parents with democratic 88.7% category. After the performed statistical tests using Sperman Rank then acquired the results of statistical tests where SIGs 0.0002 GIS < α (0.05), which means there is a connection between parenting parents with nutritional status on toddlers in the village of Selokgondang Sub Lumajang Sukodono. Obtained most of the parenting parents is democratic and most experienced good nutritional status. Health care personnel should enhance public awareness by providing counseling on the importance of parenting parents the nutritional needs on toddlers, thus reducing the problem of nutritional status